37 You want my advice and guidance? performance of a cardiology email advice line to general practitioners. (May 2019) - Belsham, John; Wilson, David G; Foster, Will; Trevelyan, Jasper; Aldhoon, Bashar; Smith, David; Goyal, Deepak; Roberts, William; Formisano, Francesco; Taylor, Robin; Miles, Charlotte; Tudor, John; et al.
Abstract : Background: Cardiologists at Worcestershire Royal Hospital have provided email advice and guidance for local general practitioners. The performance of this service has not been formally evaluated. Methodology: Data were collected prospectively throughout 2018 including patient demographics, GP practice, time/date of email and of response, the person responding, the nature of the clinical question and whether admission or clinic appointment was recommended. Patient records were reviewed two months after the email to evaluate outcome. Results: In 2018, 2157 email queries were received about patients with a median age of 68 years (IQR 53–77). 52% were male. In total 2145 queries (99.44%) were sent on weekdays, mean of 8.25 per weekday. The median response time was 4 hours 19 minutes (IQR 1.78–17.45 hours), 14.6% received a response in under an hour, 86.1% of queries were responded to within 24 hours and 93.9% within 48 hours. Weekend emails explained the remainder. Overall 91.4% of emails were received between 0800–1700 and 36.2% of responses were sent outside of this time. We estimate 215 consultant hours were taken replying (assuming 6 minutes/email) equivalent to 54 programmed activity (PA) episodes. The most common queries related to interpretation or management of ECGs (44%), ambulatory ECG monitoring (12.5%) or echocardiography (9.2%). In total 73 GP Practices sent emails (mean of 28.6 queries/practice) of which 63 (86.3 %) were from the Worcestershire CCG area. Worcestershire GPs accounted for 97.5% of all queries. Variation exists between individual practices: three did not send any email queries; seven sent only one query over the year and one practice sent 179 queries (8.6% of total). If all practices participated as frequently, the number of emails received would increase five-fold to over 10, 000 a year. Of the 10 Cardiology consultants within the deparment, not all participated equally with three consultants replying to 63% of all emails and one replying to 30%. Admission to hospital was recommended in one case and referral to outpatient clinic was recommended in 501 of 2152 cases (23.2%). Of these, a referral was only received within two months in 60.6% of cases. We estimate that this initiative avoided up to 1493 clinic appointments (124 Consultant PA episodes or 2 per week). Potential cost savings to CCG (1493 × £168 for cost of new outpatient consultation) = £250, 824. Potential revenue to cardiology for ECG interpretation (44% of 2153 × £25 = £23, 683) and for 24 hour holter interpretation 12.5% of 2153 × £45 =£12, 110) (Price estimate from NICE Remote ECG interpretation consultancy services for cardiovascular disease MIB152)) Conclusion: A cardiology advice and guidance email service is highly efficient use of specialist consultant time with a large number of outpatient clinic appointments being avoided at a cost saving to the CCG. Conflict of Interest: None